2003
DOI: 10.4049/jimmunol.170.3.1291
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Antigen-Specific CTL by Recombinant HIV Trans-Activating Fusion Protein-Pulsed Human Monocyte-Derived Dendritic Cells

Abstract: Several systems have been tested for introduction of Ags into human dendritic cells (DC). Most of them to date, however, are complex and possess limited efficiency. Recent advances in HIV trans-activating (TAT) fusion protein technology permit extremely high transduction efficiencies for a majority of mammalian cell types. Here we report our attempts to develop a simple, but highly efficient, protocol for loading of antigenic protein into DC using TAT fusion technology. A TAT-minigene fusion protein was genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Other investigators have also reported potent immune responses using Tat-PTD as a vehicle to deliver tumor and viral antigens into dendritic cells (38). Vaccination of mice with melanoma-specific antigen-transduced monocyte-derived dendritic cells by TATmediated protein has been shown to generate durable and robust CTL responses, which regresses tumors (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators have also reported potent immune responses using Tat-PTD as a vehicle to deliver tumor and viral antigens into dendritic cells (38). Vaccination of mice with melanoma-specific antigen-transduced monocyte-derived dendritic cells by TATmediated protein has been shown to generate durable and robust CTL responses, which regresses tumors (39).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination of mice with melanoma-specific antigen-transduced monocyte-derived dendritic cells by TATmediated protein has been shown to generate durable and robust CTL responses, which regresses tumors (39). Tanaka et al observed that a TAT fusion protein with HER-2/neu generated efficient CTL responses in contrast to the poor CTL generation observed without the presence of a TAT PTD (38). Furthermore, TAT-fusion proteins do not only induce specific CTLs but also generate potent T-helper cell responses due to simultaneous loading of the HLA class II pathway of antigen processing and presentation (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the RGD domain, Tat contains in its sequence a short and highly basic region (aa 47-59) termed "protein transduction domain" (PTD), a feature shared with very few other proteins called "penetratins" [201,202], which enables Tat-or PTDconjugated proteins to efficiently enter the cells in an energy-and receptor-independent fashion [203,204]. Thereby, the PTD peptide or the Tat protein have been largely used to deliver conjugated antigens to the MHC class I restricted-antigen presentation pathway, and to increase CTL responses to the conjugated antigen [187,[205][206][207][208][209][210]. It has also been suggested that the PTD domain itself, in addition to its antigen-delivery capability, exerts an adjuvant effect on the conjugated antigen, in a fashion similar to poly-L-arginine peptides [211], leading to increased expression of specific MHC-I/peptide complexes and activation of T cell responses [202].…”
Section: Immunomodulatory Activity Of Hiv-1 Tatmentioning
confidence: 99%
“…[4][5][6][7][8][9] PTDs can even deliver bulky molecular cargos (>100 kDa) into a wide variety of cell types. [10][11][12][13] However, to use PTDs as effective intracellular drug delivery carriers with clinical applications, it is necessary to create novel PTDs with greater protein-transduction potency than exists naturally.…”
Section: -3)mentioning
confidence: 99%